PENGEMBANGAN PERANGKAT PEMBELAJARAN PADA MATERI SEGIEMPAT MELALUI PENDEKATAN OPEN-ENDED UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF - Yanti Yanti; Sumarni Sumarni; Nuranita Adiastuty (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2019)
The study aims to develop learning devices through an open-ended approach in square material. The learning devices developed consist of student modules and lesson plan (RPP). This study is the research, development model of Plomp with consist of three stages: preliminary research phase, prototype phase and assessment phase. Techniques of data collection that used were pretest and posttest questions, questionnaire  of expert validation and questionnaire of student response. The device developed was validated by three validators then conducted a limited trial. From the resulting validation data the average score of student module is 4.33 (valid), the average RPP score is 4.29 (valid). The validator statement against both learning devices developed is usable with little revision and without revision and the student's response to the learning device  was positive (practical). The increase of students ' creative thinking capability of N-Gain of 0.67 with moderate upgrade category. The results of the study were obtained that the device was developed is valid, practical, and can improve creative thinking ablity.